The Significance of Enterprise Resource Planning (ERP) Systems in Aviation Industry - Sherzad Ramadhan; Hassan Koutaini; Karwan Ali Ali (European Scientific Journal, ESJ, 2019)
Rapid globalization has introduced several problems in the business environment. These problems have added complexities in decision-making and intensified competition. As a result, organizations are forced to come up with comprehensive ways of mitigating the challenges. That together with the ever-changing needs of the airlines’ customers have heightened the value attached to information systems as a way of solving problems and gaining competitive advantage. Enterprise Resource Planning (ERP) system is one of the most popular systems in many organizations. However, some organizations have reported negative feedback pertaining its value. In this view, the primary objective of this study is to discern the significance of ERPs in the aviation sector. The study will accomplish that goal by focusing the research on Kenya Civil Aviation Authority, Delta Airlines, United Airlines, and the aviation sector of the Kingdom of Saudi Arabia. These cases were selected because they have successfully implemented ERP and experienced several challenges before they successfully implemented the system. The study employed secondary research methods to collect data. Literature affiliated to the topic of study particularly materials that focused on the selected cases were utilized. Critical analysis was conducted and the findings presented. To increase validity and reliability, Nvivo software was used whereby interpretive and intuitive methods were utilized. The software method gave similar results as those obtained through manual methods.